Mindfulness Meditation Improves Visual Short-Term Memory. Issue 4 (August 2021) - Youngs, Molly A.; Lee, Samuel E.; Mireku, Michael O.; Sharma, Dinkar; Kramer, Robin S. S.
Research into the effects of mindfulness meditation on behavioral outcomes has received much interest in recent years, with benefits for both short-term memory and working memory identified. However, little research has considered the potential effects of brief mindfulness meditation interventions or the nature of any benefits for visual short-term memory. Here, we investigate the effect of a single, 8-minute mindfulness meditation intervention, presented via audio recording, on a short-term memory task for faces. In comparison with two control groups (listening to an audiobook or simply passing the time however they wished), our mindfulness meditation participants showed greater increases in visual short-term memory capacity from pre- to post-intervention. In addition, only mindfulness meditation resulted in significant increases in performance. In conclusion, a single, brief mindfulness meditation intervention led to improvements in visual short-term memory capacity for faces, with important implications regarding the minimum intervention necessary to produce measurable changes in short-term memory tasks.